The Role Of Transformational Leadership On Sustainable Performance Mediated By Innovation - Anggraini, Ratih; Andrian; Nainggolan, Ferdinand (Jurnal Manajemen (Edisi Elektronik), 2025)
Innovation is a crucial factor for the sustainability of MSMEs, especially in facing market dynamics and increasing competition. This study aims to examine the impact of transformational leadership on the sustainable performance of MSMEs in Batam, considering innovation as a mediating variable and external social capital as a moderating variable. Data were collected through a survey and analyzed using a structural model with the Smart-PLS method. The results of the study indicate that transformational leadership significantly enhances innovation, which subsequently has a positive impact on the sustainable performance of organizations. External social capital strengthens the relationship between transformational leadership and sustainable performance. Innovation serves as a strong mediator in this relationship. The reliability of the research model is supported by high Cronbach's Alpha and Composite Reliability values, as well as R Square values that indicate the variation explained by the model. The validity of the model is also supported by AVE, outer loading, and HTMT values that meet the standards. The low SRMR value and high GoF value reflect the model's fit with the observed data. This study accepted all seven hypotheses with significant p-values (<0.05). Transformational leadership significantly influences innovation and sustainable performance. Innovation also significantly affects sustainable performance. External social capital significantly moderates the influence of transformational leadership on sustainable performance, both directly and through innovation.